Edukasi Tentang Diabetes Melitus dan Pemanfaatan Kayu Manis sebagai Tanaman Obat Antidiabetes Kepada Masyarakat - Ida Musfiroh; Gofarana Wilar; Eka Rosalianti; Almira Agustini Hadirana; Zahra Siti Hanifah (Indonesian Journal Publisher, 2022)
The number of people with diabetes mellitus is increasing every year, even statistics show that in 2020 Indonesia is ranked 7th in the world. Many people still do not know how to understand diabetes mellitus and a healthy lifestyle, as well as the use of medicinal plants as antidiabetic. The use of herbal medicine has many advantages. One type of medicinal plant that is effective as a diabetes treatment therapy in the Indonesian Traditional Medicine Formulary (FROTI) is cinnamon. This activity has the aim of providing socialization and education to the public in the health sector about diabetes mellitus and anti-diabetic medicinal plants, especially cinnamon which is developed in dye bags. The implementation method is carried out virtually, considering the current state of the COVID-19 pandemic, with 3 stages, namely the planning stage, the implementation stage and the follow-up stage. The result of this PPM activity is the implementation of online seminars and education through infographic posters and videos and shows that the public is becoming more educated in their knowledge about diabetes treatment efforts by utilizing various types of medicinal plants and how to process them. The results of this activity can be concluded that the education and information activities carried out can increase public understanding and knowledge about diabetes mellitus, as well as understanding of various types of antidiabetic medicinal plants that can be utilized by the community .This is based on the results of the pre-test and post-test as a measure of the success of this PPM activity.